Exploring Quezon City’s Food System: A Virtual Video Tour of Food Markets, Urban Agriculture and Sustainability - Bertuso, Arma; Prain, G. (CGIAR System Organization, 2024)
Quezon City, one of the bustling metropolises of the Philippines, is famous for its dynamic urban landscape, thriving businesses, and cultural landmarks. But beneath the surface of this classic city skyline lies a complex, vibrant food system that feeds the millions of residents daily. A new and captivating virtual video tour – “Follow the Gulay” has opened a window into this complex food ecosystem, offering viewers a deeper understanding of how food flows through the city. This immersive experience is a visual journey, blending stunning aerial shots with insightful interviews, guiding us through the various layers of food production, distribution, and consumption – revealing the interconnectedness of its various components and the pivotal role each player has in maintaining a steady food supply.